The importance of technical knowledge in sustainability of Malay bird's nest industry in Malaysia - Wan Khairy Wan Ibrahim; Mohd Rafi Yaacob; Azwan Abdullah (TextRoad Publication, 2015)
This paper discusses the importance of the knowledge in managing swiftlets’ houses as well as the science husbandry behind the sustainability of birds’ nests in Malaysia. The discussion of this paper was written based on the findings of fieldworks that were conducted in 2004 at Kelantan. Interviews with five successful entrepreneurs of the bird’s nest industry have revealed proper techniques in managing the swiftlets’ houses. These skills were explored either directly or indirectly through the entrepreneurs’ involvement in the industry. This study also sought to examine the effectiveness of these skills in determining the productivity of birds’ nests. All informants stated that their knowledge in these skills played an important role in determining the sustainability of their business.